2014
DOI: 10.1016/j.jpsychires.2014.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Emotional granularity and social functioning in individuals with schizophrenia: An experience sampling study

Abstract: Previous research has shown that healthy individuals who fail to differentiate among emotional states (i.e., those with low emotional granularity; EG) have poorer social functioning (SF) than those with high EG. It is unknown, however, whether these associations extend to clinical disorders characterized by impaired SF, such as schizophrenia. In the present study, we compared SF and EG in individuals with schizophrenia and healthy controls, and then, within the schizophrenia group, we examined the links betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 48 publications
4
46
2
Order By: Relevance
“…We did not find evidence for a disconnect between positive emotion and the environment, and, in contrast to Kimhy et al (2014), we did not find that people with and without schizophrenia differed in the extent to which their positive and negative emotions were related. Our data suggest that schizophrenia is not characterized by a disconnect between positive emotion and pleasure appraisals of the environment or more independence of positive and negative emotion, but rather is limited specifically to the elevation and dysregulation of negative emotion.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…We did not find evidence for a disconnect between positive emotion and the environment, and, in contrast to Kimhy et al (2014), we did not find that people with and without schizophrenia differed in the extent to which their positive and negative emotions were related. Our data suggest that schizophrenia is not characterized by a disconnect between positive emotion and pleasure appraisals of the environment or more independence of positive and negative emotion, but rather is limited specifically to the elevation and dysregulation of negative emotion.…”
Section: Discussioncontrasting
confidence: 99%
“…These results are in line with neuroimaging studies that indicate elevated amygdala activation during neutral stimuli in schizophrenia (Anticevic et al, 2012) and reduced activation in frontal regions supporting emotional processing (Taylor et al, 2012). EMA studies support negative emotion dysregulation, finding that that people with schizophrenia report more negative emotion than people without schizophrenia (Myin-Germeys et al, 2000; Myin-Germeys, et al, 2003; Myin-Germeys et al, 2005, Oorschot et al, 2013), and, intriguingly, a recent EMA study found that people with schizophrenia evidenced less differentiation of positive and negative emotions in daily life (Kimhy et al, 2014). Although individuals typically reciprocally activate positive and negative emotion (Larson et al, 2001) people with schizophrenia may have more independent or even coactivation of positive and negative emotion.…”
Section: Introductionmentioning
confidence: 95%
“…However, the finding that the ability to be aware of, tolerate and accept emotions was predictive of how individuals with psychosis responded to stress, not only emotionally, but also with regard to symptom increase, is extremely valuable in regard to the further development of interventions for these patients. Furthermore, it underlines that these abilities are relevant to psychosis, as has also been demonstrated in two studies by Kimhy et al (2012Kimhy et al ( , 2014 who found the ability to identify and describe emotions and the ability to differentiate between different emotional states to go along with higher levels of social functioning.…”
Section: Discussionmentioning
confidence: 58%
“…Several recent studies point to ER difficulties in people with psychotic disorders: These studies found participants with psychosis to have problems in being aware of emotions (Kimhy et al, 2012(Kimhy et al, , 2014Lincoln et al, 2015a), which is a precondition for tolerating and accepting them. Compared to healthy controls, people with psychosis also use more dysfunctional and less functional strategies, for example, they tend to suppress rather than accept emotions and are less successful in using cognitive strategies to change emotions in the desired direction (O'Driscoll et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Impaired emotional awareness and use of suppression is associated with worse social functioning in individuals with a diagnosis of schizophrenia [90][91][92] and CHR individuals [93•]. Moreover, these impairments appear to contribute to symptoms and social functioning impairments over and above neurocognitive deficits [91, 93•, 94].…”
Section: Impaired Cognitive Control Of Emotion In Psychosis-spectrum mentioning
confidence: 99%